Changes in investors risk-taking behavior during Indonesian economic recession due to the Covid-19 in 2020 - Christian Hendra Setiawan; Deddy Marciano; Cristel Joy G. Cayaban (Manajemen dan Bisnis, 2022)
This research discusses the differences in investor risk-taking behavior in Indonesia before and during the economic recession caused by the Covid-19. This pandemic began to infect Indonesia in 2020. Investor risk-taking behavior consists of three criterias, that are return expectation, risk tolerance and risk perception. Factors that can influence investor risk-taking behavior in this study are the economic recession itself and the characteristics of investors. While the characteristics of investors are seen from their status, namely age, gender, work status, marital status, education level, income, net worth and length of investment. In this study, questionnaires were distributed targeting investors in Indonesia. It was found that in fact the Covid-19 pandemic caused changes in investors risk-taking behavior, which included returning expectations and risk tolerance to decrease and risk perception to increase. Characteristics of investors Indonesian in general, it has no effect on investors' risk-taking behavior. Of the ten characteristics of investors, only two correlates with one of the criteria, namely profession and gender. It was found that the characteristics of investors did not have a positive effect because the majority of investors in this study were members of investment, money markets and capital markets communities. They join many of these communities, so that the exchange of information and discussions between one community and another will be affected. Investors’ decision making also based on the results of discussions in the community.